الثقافة العربية وشروط الولوج إلى مجتمع المعرفة - دوش, الهادي (University of Eloued جامعة الوادي, 2016)
يرتبط الوصول إلى مجتمع المعرفة بتحقيق شروط أداء التنافس العالي، ذلك أن مجتمع المعرفة تعتبر رهان وجود وضمان مستقبل، حيث أنه يرتبط بإيجاد مناحات كفيلة في ميدان إنتاج المعرفة وتحيلها وشروط تأسيسها وصولا إلى نشرها وتوظيفها، وفي هذا الإطار نجد أن الثقافة العربية بشروطها التأسيسية لا تفتقد إلى هذا المبدأ من حيث استعمال التراث الفكري والاجتهاد الإسلامي والتجديد اللغوي، غير أن التحدي الأساسي في هذا الجانب خصوصا ما تعلق بمسألة التراث الفكري وتجديده باعتباره سؤال النهضة ومدخل الإصلاح يكمن في المنهج وكيفية الاشتغال عليه. ABSTRUCT : The access to the knowledge society is linked to the achievement of performance conditions of higher competition. The knowledge society is considered proof of the existence and ensure the future, where it is linked to the creation of a climate capable in the field of knowledge production, analysis it, and its terms knowledge founding, finally the dissemination of knowledge and using them. In this context, we find that the Arab culture with the founding conditions do not lacking this principle in terms of the use of intellectual heritage, Islamic jurisprudence, and Linguistic renewal. However, the fundamental challenge in this regard especially regarding the issue of intellectual heritage is the approach and how to engage in it.
Arab culture and conditions of access to the knowledge society
مجلة البحوث والدراسات المجلد 13 العدد 01 جامعة الوادي
Keywords: الثقافة، العروبة، المعرفة، التراث، الفكر المعاصر، الإصلاح الاجتماعي; culture, Arabism, knowledge, heritage, contemporary thought, social reform